A qualitative exploration of the dropout rate of provincial female swimmers between the age of 18 and 30 years old in KwaZulu-Natal - Schutte, Dawn-Abigail (The IIE, 2020)
The general trend in swimming reveals that most female athletes drop out of swimming between the ages of 18 and 30 years old; therefore exploring the factors that contribute to the dropout rate will enable insight and understanding to be gained. As a result, women remain underrepresented in all sports in the country. This study sought to investigate the high dropout rates of female swimmers, which included gaining insight and understanding of the various factors that contribute to a female swimmer’s dropout rate. The data collection methods used included in-depth semi-structured interviews with three purposively selected participants, which enabled the study to produce thick narratives allowing for an in-depth analysis to occur. Findings indicated that all participants displayed high levels of intrinsic motivation, although it was often the influence and impact of extrinsic motivators that lowered the participant’s intrinsic motivation and self–determination leading to their drop out in swimming. Findings indicated that there is a need for psychological and social support for female swimmers within the swimming sphere. It is recommended that support systems such as mentors and sports psychologists be implemented within the field of swimming, providing support to female athletes. A further study could explore ways in which this can be done in a cost-effective manner.
Keywords: Motivation; Swimming; Dropout rates; Female swimmers; Academic career; Overtraining; Injury; Burnout